Expressed humility in inter-organization interactions: Why and when boundary-spanning leaders’ expressed humility can promote partner cooperation commitment - YANG, Wenhao (Institutional Knowledge at Singapore Management University, 2023)
In an organization, expressing humility can promote more meaningful and satisfying relationships with others. Given its potentially positive effects, researchers have been interested in studying the promotion and management of expressed humility for decades. Although there is some literature on the mechanism of expressing humility within an organization, none of them has pointed out the positive effects of expressed humility between organizations represented by their boundary-spanning leaders. Specially, no research efforts have been devoted to understanding how expressed humility between partners affects the economic behavior and outcomes of organizations and when it is effective for positive effects. In this paper, I focus on the impact of partner relationship between boundary-spanning leaders. I propose that expressed humility is an effective tool for promoting interpersonal relationships, which ultimately strengthen organizational ties. However, since humility is a social norm, it can be challenging for the other party to judge whether the humility expressed by leaders is sincere or not. Therefore, this paper uses attribution theory to explain the different impacts of leaders’ expressed humility on inter-organizational cooperation commitment through attributed motives. To test the research model, I collected multiple sources of data from 248 pairs of leaders and their followers who have relevant experiences working as leaders of organizations in bilateral business projects. Results from the main analyses and a series of supplementary analyses indicate that partner’s expressed humility has a positive mediated effect on inter-organizational cooperation commitment through knowledge sharing. Moreover, results from the moderating effect analyses show that attributed-motive for performance improvement has a moderating effect on the positive relationship between expressed humility and inter-organizational cooperation commitment. However, when the leader’s humility is attributed-motive for impression management, expressed humility does not have a significant effect on the relationship between expressed humility and inter-organizational cooperation. The paper provides insights into how boundary-spanning leaders can build stronger organizational relationship and offers managerial implications for organizations in the inter-organizational exchange in emerging markets. Overall, this study contributes to the literature by providing a nuanced understanding of the impact of interpersonal relationships on inter-organizational cooperation commitment in the Chinese context.